Acoustic radiation force impulse elastography findings of achilles tendon in patients with hypothyroidism - Feride Altay; Hale Turnaoğlu; Feride Kural Rahatlı; Yusuf Bozkuş; Özlem Turhan İyidir; Kemal Murat Haberal (Turkish Journal of Internal Medicine, 2021)
Introduction The aim of our study was to investigate the effect of thyroid dysfunction on tendons and the contribution of Acoustic Radiation Force Impulse (ARFI) elastography to the diagnosis of tendinopathy. Methods Eighty Achilles tendons of 40 patients under levothyroxine treatment, who had previously known hypothyroidism but high serum thyroid stimulating hormone levels, and 80 Achilles tendons of 40 healthy individuals were evaluated with ARFI (Virtual Touch Quantification®). 19 of 40 of the patients with hypotiroidism’ Achilles tendons were re-evaluated after thyroid stimulating hormone levels reached to normal limits following the adjustments in thyroid hormone replacement therapy. The middle portion of the each Achilles tendon was chosen for the examination. Every examination consisted of three to five independent measurements (shear wave velocity- meters per second). The mean shear wave velocity value was calculated for each tendon, and used for statistical analysis. Results The stiffness values of both left and right Achilles tendons, represented as shear wave velocity, were similar in patients with hypothyroidism and control group. There was no significant difference between the Achilles tendon shear wave velocity measurements of 19 of 40 hypothyroidism patients who were re-evaluated after the adjustments in thyroid hormone replacement therapy. Conclusions The lack of significant difference in Achilles tendon stiffness between non-naive hypothyroid patients and the control group may be explained as a positive clinical effect of thyroid hormone replacement therapy.